Sesquiterpenes from Rhizomes of Cyperus rotundus with Cytotoxic Activities on Human Cancer Cells in vitro. Issue 10 (October 2015) - Ryu, Byeol; Kim, Hye Mi; Lee, Jae‐Seung; Cho, Yoon Jin; Oh, Myung Sook; Choi, Jung‐Hye; Jang, Dae Sik
Abstract Two new sesquiterpenes, cyperusol A3 (1) and 3β‐hydroxycyperenoic acid (2), along with three known sesquiterpenes, britanlin E (3), 1β, 4α‐dihydroxyeudesm‐11‐ene (4), and 11, 12‐dihydroxyeudesm‐4‐en‐3‐one (5), were isolated from the AcOEt‐soluble fraction of rhizomes of Cyperus rotundus L. The structures of 1 and 2 were elucidated by physical and spectroscopic methods (1H‐ and 13C‐NMR, 2D‐NMR, and MS). All of the isolates, 1–5, were evaluated for their cytotoxic activities against human ovarian cancer cells (A2780) and endometrial adenocarcinoma cells (Ishikawa) using MTT assays.